Neuropsychiatric and Neurocognitive Manifestations in HIV-Infected Children Treated With Efavirenz in South Africa—A Retrospective Case Series - Hammond, Charles K.; Eley, Brian; Ing, Natalia; Wilmshurst, Jo M. (Frontiers in Neurology, 2019)
Background: Efavirenz is associated with transient neuropsychiatric manifestations but the impact on neurocognition in children is unknown. Genetically slow metabolizers of efavirenz may be at risk of toxicity. This study describes neuropsychiatric and neurocognitive manifestations of South African children with suspected efavirenz neurotoxicity. Method: This retrospective study describes clinical features of 12 children with features consistent with efavirenz neurotoxicity between 2008 and 2014. Results: Twelve children (4 males, 8 females) aged 3.3-12 years (median 8.4 years) were referred to a dedicated pediatric neuroHIV service. Eight were of indigenous African (black) ancestry and 4 were of mixed ancestry. Two children (both of black ancestry) were phenotypically slow metabolizers and presented with drowsiness, seizures, sleep disturbances, ataxia and slurred speech. They had high plasma efavirenz concentrations above normal range resulting in discontinuation of efavirenz. Ten other children had clinical presentations compatible with efavirenz neurotoxicity. The acute neuropsychiatric manifestations were noticed 2-8 weeks (mean 5 weeks) after commencing efavirenz and resolved over a few weeks. Nine children had neurocognitive deficits and showed poor performance in all neurocognitive domains. Exacerbation of these features due to prolonged efavirenz administration (6-72 months; mean 31 months) could not be excluded. Interpretation: Efavirenz causes transient neuropsychiatric adverse effects and may contribute to poor long-term neurocognitive outcomes in HIV-infected children. Prospective studies comparing efavirenz-treated and efavirenz-naïve children are needed.